2020
DOI: 10.2486/indhealth.2018-0205
|View full text |Cite
|
Sign up to set email alerts
|

A novel vest with dual functions for firefighters: combined effects of body cooling and cold fluid ingestion on the alleviation of heat strain

Abstract: This study investigated the separate and combined effects of skin cooling and cold fluid ingestion on the alleviation of heat strain when wearing protective firefighting clothing at an air temperature of 30°C with 50%RH. A vest with the dual functions of cooling and providing sports drink supply (1.2% body mass) was developed. Eight males participated in the following four conditions: control [CON], drinking only [DO], cooling only [CO], and both cooling and drinking [CD]. The results showed that rectal (T re)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
3
1
0
Order By: Relevance
“…During the post-exercise recovery, there were faster rates of fall in lower-body as well as upper-body skin temperatures in FCJ trial in comparison to CON trial ( Table 1 ). These findings are consistent with previous studies that used upper-body cooling with an ice-vest ( Kim et al, 2020 ) or whole-body fanning ( Carter et al, 1999 ). These studies have reported lower-body as well as upper-body skin temperatures during the post-exercise recovery in compensable (30°C) ( Kim et al, 2020 ), or uncompensable (40°C) ( Carter et al, 1999 ) heat stresses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During the post-exercise recovery, there were faster rates of fall in lower-body as well as upper-body skin temperatures in FCJ trial in comparison to CON trial ( Table 1 ). These findings are consistent with previous studies that used upper-body cooling with an ice-vest ( Kim et al, 2020 ) or whole-body fanning ( Carter et al, 1999 ). These studies have reported lower-body as well as upper-body skin temperatures during the post-exercise recovery in compensable (30°C) ( Kim et al, 2020 ), or uncompensable (40°C) ( Carter et al, 1999 ) heat stresses.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies that used upper-body cooling with an ice-vest ( Kim et al, 2020 ) or whole-body fanning ( Carter et al, 1999 ). These studies have reported lower-body as well as upper-body skin temperatures during the post-exercise recovery in compensable (30°C) ( Kim et al, 2020 ), or uncompensable (40°C) ( Carter et al, 1999 ) heat stresses. These observations may indicate that the fan cooling jacket use reduces whole-body skin temperature quickly while promoting falls in upper-body skin temperature within less than 5 min and lower-body skin temperature at more than 5 min but less than 10 min during recovery following exercise under our experimental settings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Precooling is an effective way to reduce heat strain. The combination of external precooling such as the use of a cool-vest [31] and internal precooling, such as ingesting cold drinks [32] or ice-slurry [33] lowers the body heat content, thus providing a heat sink [34]. Ice slurry ingestion studies have not addressed patterns of consumption in habitual users of this strategy but typically assessed it as an intervention amongst athletes/ workers that are accustomed to drinking cold water but less accustomed to large volumes of ice slurry.…”
Section: Preventive Measures For Heat Strain and The Relation With Covid-19mentioning
confidence: 99%